2022
DOI: 10.1021/acs.jctc.2c00218
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Orbital Minimization Method for Excited States Calculation on a Quantum Computer

Abstract: We propose a quantum-classical hybrid variational algorithm, the quantum orbital minimization method (qOMM), for obtaining the ground state and low-lying excited states of a Hermitian operator. Given parametrized ansatz circuits representing eigenstates, qOMM implements quantum circuits to represent the objective function in the orbital minimization method and adopts a classical optimizer to minimize the objective function with respect to the parameters in ansatz circuits. The objective function has an orthogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…OptOrbVQE could easily be generalized to "Op-tOrbMC-VQE" or "OptOrbSSVQE" by modifying eq 9 to be a weighted sum of the transformed Hamiltonian with respect to mutually orthogonal parametrized states in the same manner as these methods. Orbital optimization could also be applied to the quantum Orbital Minimization Method (qOMM) 34 by modifying eq 9 in an analogous way. These methods all find low-lying excited states simultaneously through the minimization of a single objective function.…”
Section: Discussionmentioning
confidence: 99%
“…OptOrbVQE could easily be generalized to "Op-tOrbMC-VQE" or "OptOrbSSVQE" by modifying eq 9 to be a weighted sum of the transformed Hamiltonian with respect to mutually orthogonal parametrized states in the same manner as these methods. Orbital optimization could also be applied to the quantum Orbital Minimization Method (qOMM) 34 by modifying eq 9 in an analogous way. These methods all find low-lying excited states simultaneously through the minimization of a single objective function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a previous work by the authors, it was demonstrated that the convergence quality of state-averaged eigensolvers such as SSVQE in a fixed basis is highly sensitive to the ansatz expressiveness and choice of circuit initialization (compared to the ground-state VQE problem and the overlap-based qOMM excited-state solver). 32 In this work, we investigate the extent to which analogous observations hold true for the orbital-optimized case as well.…”
Section: Introductionmentioning
confidence: 86%
“…SSVQE is tested with CIS and CISD as well as an "excited Hartree−Fock" initialization used in a previous study by the authors. 32 This initialization applies single-particle Fermionic excitations to the Hartree−Fock state and chooses the resulting Slater determinants with the lowest energy to initialize the circuit. Such states are orthogonal and can thus be used with both MCVQE and SSVQE.…”
Section: And Ansatz Expressivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Many works have focused on the ground state preparation of a Hamiltonian. [9][10][11][12][13] For instance, the earlier work using quantum phase estimation prepares the ground state by projecting a guess state onto the ground state. [14] However, the long coherence time and high-fidelity gates render it impractical for noisy intermediate-scale quantum (NISQ) devices.…”
Section: Introductionmentioning
confidence: 99%